Virological remission after antiretroviral therapy interruption in female African HIV seroconverters. (1st February 2019) - Gossez, Morgane; Martin, Genevieve Elizabeth; Pace, Matthew; Ramjee, Gita; Premraj, Anamika; Kaleebu, Pontiano; Rees, Helen; Inshaw, Jamie; Stöhr, Wolfgang; Meyerowitz, Jodi; Hopkins, Emily; Jones, Mathew; et al.
Abstract : Introduction: There are few data on the frequency of virological remission in African individuals after treatment with antiretroviral therapy (ART) in primary HIV infection (PHI). Methods: We studied participants ( n = 82) from South Africa and Uganda in Short Pulse Antiretroviral Treatment at HIV-1 Seroconversion, the first trial of treatment interruption in African individuals with PHI randomized to deferred ART or 48 weeks of immediate ART. All were female and infected with non-B HIV subtypes, mainly C. We measured HIV DNA in CD4 + T cells, CD4 + cell count, plasma viral load (pVL), cell-associated HIV RNA and T-cell activation and exhaustion. We explored associations with clinical progression and time to pVL rebound after treatment interruption ( n = 22). Data were compared with non-African Short Pulse Antiretroviral Treatment at HIV-1 Seroconversion participants. Results: Pretherapy pVL and integrated HIV DNA were lower in Africans compared with non-Africans (median 4.16 vs. 4.72 log10 copies/ml and 3.07 vs. 3.61 log10 copies/million CD4 + T cells, respectively; P < 0.001). Pre-ART HIV DNA in Africans was associated with clinical progression ( P = 0.001, HR per log10 copies/million CD4 + T cells increase (95% CI) 5.38 (1.95–14.79)) and time to pVL rebound ( P = 0.034, HR per log10 copies/ml increase 4.33 (1.12–16.84)). After treatment interruption, Africans experienced longer duration of viral remission than non-Africans ( P < 0.001; HR 3.90 (1.75–8.71). Five of 22 African participants (22.7%) maintained VL less than 400 copies/ml over a median of 188 weeks following treatment interruption. Conclusion: We find evidence of greater probability of virological remission following treatment interruption among African participants, although we are unable to differentiate between sex, ethnicity and viral subtype. The finding warrants further investigation. Abstract : Supplemental Digital Content is available in the text